The Local Wisdom of the Mbaba Belo Selambar Tradition of the Karo Community in the Village of Tanjung Langkat, Sub-District of SalapianLangkat Regency North Sumatra: Anthropolinguistic Studies - Indah Permatasari, Nova; Sibarani, Robert; Pujiati, Pujiati (International Journal of Educational Research & Social Sciences, 2021)
This study aims to describe the local keraifan in the tradition ofmbababeloselambar in the karo community in the village ofTanjungLangkat, sub-district of Sal Api, district of LangkatPovinsi NorthSumatra. Local wisdom in the tradition of mbababeloselambar can be seenin each of the stages that exist in the tradition. Local wisdom is a culturalheritage that always exists in a tradition and can be preserved forgenerations to come. The method used in this tradition is the qualitativemethod. The data used in this research is local wisdom that exists in thistradition. The results of this study are there are five (5) local wisdoms thatexist in the tradition of mbababeloselambar, namely hard work, kinship,courtesy, harmony, responsibility and commitment.